Executive Committee Minutes 2012-08-23 - Academic Senate:::::::::
Approval of Agenda. Approval of Minutes of 5/3/12 and 6/14/12. Correspondence received. Chair Report. President Report. Provost Report. Suggestion to charge Senate Diversity Subcommittee with oversight GSSEW recommendations – item referred to SDS. Faculty Eligible for Emeritus Status approved for Senate consent calendar. Statewide Senator Report. Endorsement of ASCSU's Resolution on Prop. 30 – approved for Senate agenda. Vice Chair Report. Vice President of Administrative and Finance Report. APC Report. EPC Report. FSAC Report. SAC Report. Associated Students Report. Senate agenda approved.